The Role of the Basal Plate during the Development of Oriental Hybrid Lily ‘Sorbonne’ - Wu, Shasha; Liu, Xiaohua; Zhang, Qixiang; Lu, Yingmin (2012)
The ultrastructure and function of the basal plate in terms of metabolite translocation in lily bulb during bulb growth and development was investigated. The ultrastructure of the basal plate was observed under transmission electron microscopy (TEM) while translocation studies made use of the analysis of 6(5)-carboxyfluorescein (CF) diacetate in various tissues in the basal plate using laser confocal microscopy. TEM revealed that starch grains and three forms of vegetative storage proteins (protein-body-like organelles, granular and flocculent protein) were observed in the parenchyma cells. The granular and flocculent proteins fused to increase their sizes and to form the protein body-like organelles after anthesis. Starch content decreased gradually from planting to anthesis and then increased until leaves and shoot became senescent. CF was translocated between the scales and the stem through the phloem strands in the basal plate, which indicates the important translocation function of the basal plate. In conclusion, the basal plate plays an important role in transporting metabolites among scales which are attached to the basal plate and between scales and shoots. The parenchyma cells were not only involved in facilitating the transport process but also functioned as the site of temporary storage.
Keywords: Lilies (Plant); Plant growth promoting substances